Forlorn migrants : an international legal regime for undocumented migrant workers - Ahmed, Syed Refaat (Dhaka : University Press, 2000)
Study examines the policy responses of Bangladesh to the clandestine emigration of its workers to Malaysia and India.
Includes bibliographical references (p. [253]-263) and index.
Keywords: Immigrants -- India, Northeastern .; India -- Emigration and immigration; Bangladesh -- Emigration and immigration